2016
DOI: 10.1093/jjco/hyw074
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of children and their parents about the pain experienced during their hospitalization and its impact on parents’ quality of life

Abstract: Parental reports tended to underestimated children's pain, especially acute pain. The sex of children, the age and the marital status affect the perceptions of both children and their parents about pain. The parental quality of life is affected especially when the pain is caused by life-threatening diseases such as cancer. However, it improves as the treatment of their children is completed with no complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
1
17
0
3
Order By: Relevance
“…A systematic review of 12 studies in rheumatoid arthritis (11,879 patients) reported considerable discordance between patient and professional rating of global assessment, with patient estimate of a worse state, driven by pain and function [13]. Children reported higher acute pain scores than their parents [33]. It has been argued that professionals can become "numb" to suffering [47].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 12 studies in rheumatoid arthritis (11,879 patients) reported considerable discordance between patient and professional rating of global assessment, with patient estimate of a worse state, driven by pain and function [13]. Children reported higher acute pain scores than their parents [33]. It has been argued that professionals can become "numb" to suffering [47].…”
Section: Discussionmentioning
confidence: 99%
“…Três domínios sobressaíram-se nos resultados: Dor (mães subestimam as dores vivenciadas pelos filhos), Ansiedade frente aos procedimentos (mães superestimam as dificuldades dos filhos frente à necessidade de exames) e Comunicação (domínio no qual se obteve maior aproximação entre as respostas dos dois grupos). A tendência a perceber como menor a intensidade da dor vivenciada pelos filhos foi encontrada em outro estudo 21 , que investigou 251 crianças (92 com câncer) e seus pais, com o mesmo instrumento utilizado no presente estudo.…”
Section: Discussionunclassified
“…A avaliação da dor é subjetiva e pode afetar diferentes esferas da QV do paciente, e que a mãe, em especial, é peça importante no manejo desse sintoma, sendo, portanto, de fundamental importância que ela compreenda a real dimensão com que a criança vivencia sua experiência álgica 21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…demonstrated that parents are able to offer reasonable estimates of their child's pain. However, parents may tend to overestimate symptoms in acute pain conditions, while they may underestimate it in the setting of chronic disease …”
Section: Observational Pain Assessment Toolsmentioning
confidence: 99%